SAT-427 Quality of Life Following Treatment for Graves’ Disease: A Comparison of Radioactive Iodine Ablation and Surgery - Rowe, Christopher W (J Endocr Soc, 2020)
Introduction: Quality of Life (QoL) is reduced in patients with Graves’ disease, however the impact of treatment modality is unclear, with conflicting evidence from recent studies (1–3). We hypothesized that surgery would have a greater impact than radioiodine on QoL in Graves’ disease, especially with regard to the physical-symptom subdomain. Methods: Patients treated with thyroid surgery for benign disease (n=425) or radioactive iodine for hyperthyroidism (n=1637) at a single tertiary institution between 2000 and 2017 were invited to complete a validated thyroid-specific QoL instrument (City of Hope), reporting scores 0–10, where higher scores are associated with greater QoL. Responses were received from 307 patients, of whom 114 (37%) had Graves’ disease, treated with total thyroidectomy (n=23) or doses of 15mCi (550MBq) radioiodine (n=91, including 19 patients receiving 2 or more doses). The results of patients with Graves’ disease are reported here. Medians [interquartile ranges] are compared with the Mann-Whitney test (alpha 0.05). Results: 85% of respondents were female, with no difference in gender between groups (p=0.11). Thyroidectomy patients were more likely to be younger (36 [31–49] vs 50 [39–59] years, p=0.004); and have a shorter duration between treatment and survey (5.9 [2.4–9.6] vs 7.6 [4.9–11.6] years, p=0.04). No overall QoL deficit was seen in patients treated with surgery compared to radioiodine (6.8 [5.2–7.3] vs 7.0 [5.8–8.1], p=0.08). However, patients treated with surgery reported reduce QoL in psychological (6.6 [4.7–7.5] vs 7.0 [5.9–8.2] p=0.05) and social (7.9 [6.4 – 8.9] vs 8.9 [7.4–9.8] p=0.01) subdomains compared to radioiodine-only treated patients. Within the social subdomain, the QoL detriment was driven by lower scores relating to questions regarding impact on personal and family relationships, support, and isolation (p<0.001), and not by impact on activities of daily living or employment concerns. Interestingly, there was no between group difference in the physical symptom subdomain (p=0.16). QoL differences between treatment modalities were preserved when patients receiving multiple doses of radioiodine were excluded. Discussion In this non-randomised cross-sectional study from a tertiary-hospital population in Australia, a QoL deficit was demonstrable in subdomain scores for patients with Graves’ disease treated with surgery compared to radioiodine, although the overall result was not significantly different. Better understanding of patient experiences is required to guide treatment strategies and appropriately counsel patients. References (1) Torring et al. Thyroid. 2019;29(3):322–31. (2) Abraham-Nordling et al. Thyroid. 2005;15(11):1279–86. (3) Ljunggren et al. Thyroid. 1998;8(8):653–9.